A STUDY ON IMPROVEMENT OF IQ LEVEL IN BORDERLINE MENTALLY RETARDED CHILDREN BY THE USE OF BRAHMI GHRITA AND JYOTISHMATI TAIL - Kute, *Arun Parmeshwar; Kumari Ojha, Nisha; Kumar, Abhimanyu (International Journal of Ayurveda and Pharma Research, 2018)
Ayurveda is a life science having Prayojana (ultimate aim) prevention is better than cure and if patient is suffering from any disease then cure early. Health of body totally depends upon mind health. In Ayurvedic texts certain medications are prescribed for mental health and to treat underlying diseases such as Jadatva, Mandabuddhitva (mental retardation), which comes under the category cognitive deficit. Among various cognitive deficits, borderline mental retardation is an important entity which is a part of the cognition. In Ayurveda, there are some drugs which are more effective in mental retardation especially in the borderline mental retardation. The present research work has been planned to study only borderline mental retarded children with the use of Brahmi ghrita & Jyotishmati tail. In IQ level, the mean score before treatment was 80.06 which were increased to 81.56 after treatment showing 1.92% improvement. The result found was statistically highly significant with p value <0.001. This may be due to the Medhya prabhavas of drugs like B. monnieri and C. paniculatus which increases grasping and intellectual ability. Past studies also supports this data. B. monnieri, C. pluricaulis have proven improved learning and memory enhancing activity (intellectual functions).